Research on Helical Electrode Electrochemical Drilling Assisted by Anode Vibration for Jet Micro-Hole Arrays on Tube Walls - Tao Yang; Yikai Xiao; Yusen Hang; Xiujuan Wu; Weijing Kong (Micromachines)
The electrochemical cutting technique, utilizing electrolyte flushing through micro-hole arrays in the radial direction of a tube electrode, offers the potential for cost-effective and high-surface-integrity machining of large-thickness, straight-surface structures of difficult-to-cut materials. However, fabricating the array of jet micro-holes on the tube electrode sidewall remains a significant challenge, limiting the broader application of this technology. To enhance the efficiency and quality of machining these jet micro-holes on the tube sidewall, a helical electrode electrochemical drilling method assisted by anode vibration has been proposed. The influence of parameters, such as the rotational direction and speed of the helical electrode, as well as the vibration amplitude and frequency of the workpiece, on the machining results was investigated using fluid field simulation and machining experiments. It was found that these auxiliary movements could facilitate the renewal of electrolytes within the machining gap, thereby enhancing the efficiency and quality of electrochemical drilling. Using the optimized machining parameters, an array of 10 jet micro-holes with a diameter of 200 μm was machined on the metal tube sidewall. Electrochemical cutting with radial electrolyte flushing tests were then performed through these micro-holes.